Robotic process automation using UiPath StudioX : a citizen developer's guide to hyperautomation - Javed, Adeel; Sundrani, Anum; Malik, Nadia; Prescott, Sidney Madison (Apress, 2021)
Learn about Robotic Processing Automation (RPA) and how to build bots using UiPath. This book uses hands-on examples to explain the basics of UiPath and then walks you through real-world prototypes for testing your knowledge. Organizations around the world are implementing RPA in some capacity, and there is a shortage of RPA developers in the market. Analysts predict that the RPA market size will be worth $4 Billion by 2025. With UiPath as one of the three major players in the RPA market, professionals and students can use this book to get ahead of the curve. This book helps you kick-start your automation journey with a special focus on one of the most popular RPA tools: UiPath. Robotic Process Automation using UiPath explains in detail the various features and functionalities of the RPA platform including development, debugging, and error handling. You will: Create robots from scratch, using one of the market leaders in RPA Develop automation apps and deploy them to all the computers in your department Build, test and perform enterprise automation tasks with UiPath Understand the key building blocks and components of UiPath Apply UiPath programming techniques to deploy robot configurations Review email Automation Automate Excel and PDF interactions.